Moderasi Beragama dan Akulturasi Agama Budaya: Sebuah Dinamika Hidup Beragama di Tana Toraja: Sebuah Dinamika Hidup Beragama di Tana Toraja - Darius, Gayus; Safril, Safril (Institut Agama Kristen Negeri Toraja, 2024)
Abstract: Conflicts driven by religious backgrounds or those claiming to represent religion pose significant threats, especially in societies that are highly diverse in terms of culture, ethnicity, race, and religion. In the Toraja community, the acculturation of religion and culture, along with religious moderation, serve as two models of religious practice to address religious conflicts. This study employs a descriptive qualitative research method, focusing on the values developed through the approaches of religious moderation and religious-cultural acculturation. The findings of this research reveal that religious moderation can be integrated with local culture, particularly the value of